Developing and Evaluating a Novel Drug Delivery System, Calcium-Alginate Beads loaded with Valsartan - Salwa Saad; Haifaa Alali (College of Pharmacy University of Baghdad, 2024)
Valsartan is one of the most common drugs used by chronic patients in the management of hypertension, heart failure, and diabetic nephropathy. This present study was conducted with the aim of formulating a long-acting pharmaceutical form by preparing millimeter dimensions' solid polymeric beads using the Ionotropic Gelation technique by using the polymer "Alginate Sodium" (SA), and Calcium Chloride CaCl2 as a cross-linking agent. Prepared valsartan beads succeeded in the possibility of decreasing dose administration and therefore, reduced immediate release side effects of conventional forms of Valsartan. Valsartan beads were studied using different concentrations of Sodium Alginate and Calcium Chloride to select the optimal formula and then were compared with locally marketed film-coated tables containing Valsartan. The formula (SA 3%, CaCl2 10%) was chosen after conducting several physiochemical tests such as shape and dimensions, swelling index, entrapment efficiency, in vitro drug release, and FTIR. FTIR test showed no chemical bonding between Valsartan and other excipients. Selected beads achieved a high percentage of swelling in phosphate buffer solution pH=6.8. Entrapment efficiency was also high at about 80%. Prepared beads followed the Korsmeyer-Peppas release mechanism, and eventually obtained extended-release beads which slowed drug release for 24h, Compared with the film-coated tablets, the in vitro  release of valsartan expired after only one hour.